2011
DOI: 10.1590/s1807-55092011000200001
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos agudos de diferentes intensidades de exercício sobre a ingestão alimentar pós-exercício

Abstract: ResumoO objetivo do presente estudo foi verifi car os efeitos agudos de diferentes intensidades de exercício aeróbio (40 e 80% do VO 2pico ) sobre a ingestão alimentar pós-exercício. Participaram do estudo 18 adultos jovens, eutrófi cos (22,20 ± 1,72 kg/m²) e fi sicamente ativos. Todos os sujeitos foram submetidos aleatoriamente a três condições experimentais: controle (sem exercício); EBI, exercício de baixa intensidade (40% do VO 2pico ) e EAI, exercício de alta intensidade (80% do VO 2pico ). As sessões de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In addition to raising the EE post-exercise, some studies have demonstrated that physical exercise seems to reduce the food ingestion, through a phenomenon called "anorexia induced by exercise" 7 . The post-exercise anorexia consists of the hunger suppression that may occur after physical exercise sessions and may be quantified indirectly by scales or questionnaires [8][9] and circulating levels of the hormones involved in the central control of food intake [10][11] and directly via the quantification of food intake 6,12 . The post-exercise anorexia has been widely reported in aerobic activities with intensity above 60% of maximum oxygen consumption (VO 2max ) 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to raising the EE post-exercise, some studies have demonstrated that physical exercise seems to reduce the food ingestion, through a phenomenon called "anorexia induced by exercise" 7 . The post-exercise anorexia consists of the hunger suppression that may occur after physical exercise sessions and may be quantified indirectly by scales or questionnaires [8][9] and circulating levels of the hormones involved in the central control of food intake [10][11] and directly via the quantification of food intake 6,12 . The post-exercise anorexia has been widely reported in aerobic activities with intensity above 60% of maximum oxygen consumption (VO 2max ) 6 .…”
Section: Introductionmentioning
confidence: 99%